The Influence of Artificial Intelligence on Business Decision Efficiency in MSMEs in the Digital Economy Era - Vina Rahmayana; Renita Fitriani; Vani Rahmayani (Worldwide Research Publishing, 2025)
The development of Artificial Intelligence (AI) technology in the digital economy era has changed the way business actors make business decisions. For Micro, Small, and Medium Enterprises (MSMEs), the use of AI has the potential to increase efficiency in the process of data analysis, strategic planning, and faster and more accurate decision-making. However, the level of use of AI in MSMEs is still diverse, so it is necessary to further study its influence on the efficiency of business decisions. This study aims to analyze the influence of the use of Artificial Intelligence on the efficiency of business decision-making in MSMEs in the digital economy era. This study uses a quantitative approach with a survey method of MSME actors who have utilized digital technology in their business activities. Data collection was carried out through a structured questionnaire that was distributed to respondents. The data obtained is then analyzed using statistical analysis techniques, such as regression analysis, to determine the relationship and influence between the use of Artificial Intelligence and the efficiency of business decisions. The results of the study show that the use of Artificial Intelligence has a positive and significant influence on the efficiency of business decision-making in MSMEs. The use of AI technology helps business actors in processing market information, predicting consumer trends, and improving the accuracy of business strategies. Thus, the implementation of AI can be one of the important factors in increasing the competitiveness and operational effectiveness of MSMEs in the digital economy era.